2011
DOI: 10.1002/cc.438
|View full text |Cite
|
Sign up to set email alerts
|

Measuring student success

Abstract: Student success is at the heart of both institutional effectiveness and the community college mission, yet measuring such success at community colleges is problematic. This chapter highlights three efforts to grapple with this problem-a multistate work group of system-and state-level policymakers to create an improved set of student success measures to gauge state and institutional performance; the development of benchmarking tools to improve racial/ethnic equity in college student outcomes and improve evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…Mesogenetic, long-term change projects are fieldbased. Achieving the Dream, performance-based funding, and the "college completion agenda" are prominent examples of these (Baldwin, Bensimon, Dowd, & Kleiman, 2011).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Mesogenetic, long-term change projects are fieldbased. Achieving the Dream, performance-based funding, and the "college completion agenda" are prominent examples of these (Baldwin, Bensimon, Dowd, & Kleiman, 2011).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Further complicating the picture for community colleges, Mullin (2010) observed that transfer students, part-time students, and swirling students are not tracked or counted at all in these federal data systems. Baldwin, Bensimon, Dowd, and Kleiman (2011) agreed that the limitations of data systems on all levels (federal, state, and local) impede the assessment of student outcomes, and they also pointed to the complexity of identifying measures of student success in the community college environment. They contended that if policy makers and institutional leaders are unable to find the right measures and also disaggregate those measures by student subgroups, it will not be possible to promote and sustain access policies that are aligned with equitable outcomes.…”
Section: What About Completion?mentioning
confidence: 99%
“…Student Success. Student success was measured with a single item asking participants' average grades over the past term (Baldwin, Bensimon, Dowd, & Kleiman, 2011). Responses on the average grades item could range from 1 (below 50%) to 6 (90-100%).…”
Section: Methodsmentioning
confidence: 99%